Design and implementation of a secure cloud-based personal health record system using ciphertext-policy attribute-based encryption. (1st January 2013) - Wang, Changji; Liu, Xuan; Li, Wentao
There is an acceleration of adoption of cloud computing among healthcare enterprises. In this paper, we design and develop a patient-centric, cloud-based personal health record system based on open-source Indivo project. The developed cloud-based personal health record (PHR) system enables patients to securely store and share their personal health records in a flexible way by using ciphertext-policy attribute-based encryption mechanism.